On the Definition of Microservice Bad Smells - Taibi, Davide; Lenarduzzi, Valentina (IEEE software, 2018)
Code smells and architectural smells (also called bad smells) are symptoms of poor design that can hinder code understandability and decrease maintainability. Several bad smells have been defined in the literature for both generic architectures and specific architectures. However, cloud-native applications based on microservices can be affected by other types of issues. In order to identify a set of microservice-specific bad smells, researchers collected evidence of bad practices by interviewing 72 developers with experience in developing systems based on microservices. Then, they classified the bad practices into a catalog of 11 microservice-specific bad smells frequently considered harmful by practitioners. The results can be used by practitioners and researchers as a guideline to avoid experiencing the same difficult situations in the systems they develop.